The Causes of the Crisis of Rhetoric and Its Role in Social Discourse. In Terms of Chaim Perelman - Joanna Kiereś-Łach (Studia Gilsoniana, 2020)
This article is an attempt to answer the question about the causes of the rhetoric crisis and its role in social discourse. The theoretical basis of these considerations and their reference point is the concept of new rhetoric in terms of the contemporary rhetoric and argumentation theorist Chaim Perelman. The first part briefly describes contemporary cultural discourse that takes place in a democratized society in the era of so-called new media. It indicates that inquiry into rhetoric (which started in antiquity) is also inquiry into universal criteria for cultural discourse, as well as the timeless and supra-cultural norms and principles that regulate this discourse (taking into account ongoing social and cultural changes). The second part of the article refers directly to the position of Chaim Perelman on the crisis of rhetoric. Perelman saw the main reason for this crisis in the separation of rhetoric from philosophy. The third part characterizes the new rhetoric in terms of its novelty and timeliness, as well as its reference to classical (Aristotelian) rhetoric. The fourth part points to the application of the concept of new rhetoric in cultural discourse. It discusses Perelman’s concept of universal audience, as well as the problem of concrete and abstract values, the understanding of which by the members of a given audience does or does not enable the communication (consensus) between each other. The end of the article briefly assesses Perelman’s contribution to understanding rhetoric and his role in restoring rhetoric to its rightful place in social discourse.